Brazilian criminal organizations as transnational violent non-state actors: a case study of the Primeiro Comando da Capital (PCC) - Ferreira, Marcos Alan S. V. (Trends in organized crime, 2019)
This article aims to analyze the evolution of Brazilian criminal organization Primeiro Comando da Capital (PCC—First Command of the Capital), especially its transformation from a group advocating human rights to a transnational violent non-state actor. Created in the late 1990s by inmates at Taubate Prison, PCC is currently a key trigger of violence in South America. Since a massive attack performed in 2006 against security forces, the group continues to be highly operative, also coordinating drugs and arms smuggling in Brazil and abroad. A combination of sources supported this analysis of PCC’s evolution, mainly Brazilian official judicial minutes, NGOs reports, and news released from reputable sources. The article shows that PCC has gained strength in the 2010s, expanding illicit business operations in cooperation with other criminal groups. The results suggest that PCC’s expansion has changed significantly since their beginnings, into an actor that poses a challenge for the building of peaceful society in all of South America.